Meta-analysis of the history of the study of freshwater turtles and tortoises of Colombia (2017)
ABSTRACT : The citations contained in a recent literature review on the freshwater turtle and tortoise species of Colombia were analyzed. Publishing rates on these species have been increasing exponentially since the 1950s, although many of the publications would not be detected using internet-based literature searches. The most common topics of publications were systematics and phylogeography, nesting ecology, and management. In the 1970s and 1980s, the rate of publishing on the ecology and genetics of Colombian populations lagged behind the rate of publishing on these topics for populations of Colombian freshwater turtle and tortoise species located in other countries, but currently the production of the two regions is comparable. Also, in other countries there were trends towards publishing more over time in English and in journals with higher impact factors, but these trends were not significant for publications on Colombian populations. In Colombia, a disproportionate number of studies have been published on large-bodied species that face conservation problems. We argue that future studies of already well-studied Colombian species should focus on evaluating the effectiveness of management programs, and priority also should be given to increasing our knowledge of the many poorly-studied species in the country, especially those currently classified by the IUCN as data deficient (DD).